Initial gut microbiota composition is a determining factor in the promotion of colorectal cancer by oral iron supplementation: evidence from a murine model - Thibault Cuisiniere; Roy Hajjar; Manon Oliero; Annie Calvé; Gabriela Fragoso; Hervé Vennin Rendos; Claire Gerkins; Nassima Taleb; Marianne Gagnon-Konamna; François Dagbert; Rasmy Loungnarath; Herawaty Sebajang; et al. (Microbiome)
Abstract Background Colorectal cancer (CRC) development is influenced by both iron and gut microbiota composition. While iron supplementation is routinely used to manage anemia in CRC patients, it may also impact gut microbiota and promote tumorigenesis. In this study, we investigated the impact of initial gut microbiota composition on iron-promoted tumorigenesis. We performed fecal microbiota transplantation (FMT) in Apc Min/+ mice using samples from healthy controls, CRC patients, and mice, followed by exposure to iron sufficient or iron excess diets. Results We found that iron supplementation promoted CRC and resulted in distinct gut microbiota changes in Apc Min/+ mice receiving FMT from CRC patients (FMT-CRC), but not from healthy controls or mice. Oral treatment with identified bacterial strains, namely Faecalibaculum rodentium, Holdemanella biformis, Bifidobacterium pseudolongum, and Alistipes inops, protected FMT-CRC mice against iron-promoted tumorigenesis. Conclusions Our findings suggest that microbiota-targeted interventions may mitigate tumorigenic effects of iron supplementation in anemic patients with CRC. Graphical Abstract Video Abstract